Synthesis and Biological Activities of Nickel(II) and Cadmium(II) Complexes of Chlorohydroxyacetophenone-nitrobenzoylhydrazone: Mechanism for Formation of the Nickel(II) complex - Mohd. Ali, Hapipah; Abdul Halim, Siti Nadiah; P, Subramaniam; M. Zain, Sharifudin; Ismail, Endom (Malaysian Journal of Science, 2006)
The new Nickel(II) and Cadmium(II) complexes have been prepared in ethanol by template condensation of 4-nitrobenzhydrazide, 5-chloro-2-hydroxyacetophenone and metal acetate in the presence of triethylamine. The IR and UV spectra of the ligand and complexes indicate coordination of ligands to the metal centers. The initial product of the Nickel(II) complex is a square planar compound and upon recryctallization with pyridine, the complex has changed to octahedral geometry with coordination of the solvent molecules. The Schiff base ligand, HÃ¢â€šâ€š5-Clhap-4-NOÃ¢â€šâ€šbh was more sensitive towards the MCF-7 cells (human breast cancer cells) with ICÃ¢â€šâ€¦Ã¢â€šâ‚¬ values of 4.5 Ã‚Âµg mlÃ¢ÂÂ»Ã‚Â¹ than the unsubstituted ligand, HÃ¢â€šâ€šhapbh. However upon coordination to nickel, the activity has been reduced to the same level as the positive control drug, tamoxifen. The antioxidant properties of the Schiff base ligand (using the FTC method) exhibited higher activity than vitamin E or quercetine. However the activity is lower than the unsubstituted Schiff base ligand or the commercial antioxidant agent, BHT (butylated hydroxytoluene )